2022
DOI: 10.1002/anie.202117229
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Alloy PtWMn as a Mn Nanoreservoir for High‐Field MRI Monitoring and Highly Selective Ferroptosis Therapy

Abstract: Ferroptosis exhibits potential to damage drugresistant cancer cells. However, it is still restricted with the "off-target" toxicity from the undesirable leakage of metal ions from ferroptosis agents, and the lack of reliable imaging for monitoring the ferroptosis process in living systems. Herein, we develop a novel ternary alloy PtWMn nanocube as a Mn reservoir, and further design a microenvironment-triggered nanoplatform that can accurately release Mn ions within the tumor to increase reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 76 publications
0
39
0
Order By: Relevance
“…It is well-known that Mn-based nanomaterials can be used as contrast agents for T 1 -weighted MRI. Thus, we measured in vitro and in vivo T 1 -weighted MRI properties of VSe 2 /Mn-CS NSs. The U14 tumor-being mice were intravenously injected with VSe 2 /Mn-CS NSs, and the MRI manifestation of VSe 2 /Mn-CS NSs was scanned by in vivo magnetic resonance scanner system (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that Mn-based nanomaterials can be used as contrast agents for T 1 -weighted MRI. Thus, we measured in vitro and in vivo T 1 -weighted MRI properties of VSe 2 /Mn-CS NSs. The U14 tumor-being mice were intravenously injected with VSe 2 /Mn-CS NSs, and the MRI manifestation of VSe 2 /Mn-CS NSs was scanned by in vivo magnetic resonance scanner system (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…The above-mentioned tumor hypoxia outcome would jeopardize the efficacy of afterglow luminescence and cancer treatment. To reverse the hypoxic condition of the tumor microenvironment, significant efforts may be made in the future to develop efficient strategies to refuel O 2 in the tumor microenvironment to boost afterglow luminescence and PDT, such as delivering oxygen-saturated perfluorocarbons 56 , using oxygen producing materials 57 or developing of type I photosensitizer with less oxygen requirement 58 .…”
Section: Discussionmentioning
confidence: 99%
“…64 To improve the detection sensitivity of UHF-MRI for specific molecular or biological events, various smart stimuli-responsive nanoprobes that can be switched on or off by environmental changes have been ingeniously designed, such as chemical species (e.g., pH, oxygen, peroxynitrite, and metal ions), biological molecules (e.g., enzymes, glutathione (GSH), and tumor-related factors), and external physical conditions (e.g., NIR light and ultrasound). 30,[65][66][67][68][69][70][71][72][73][74][75][76] For in situ self-assembly of nanoprobes in physiological conditions, a simple and effective approach is to modify the assembly moieties with response modules, where the response module can be removed under specific stimuli, and then the assembly moiety can accomplish self-assembly by noncovalent interactions (including van der Waals forces, electrostatic interaction forces, dipole-dipole interactions, hydrogen bonding, and hydrophobic interactions), which can effectively maintain the structure and morphology of the assemblies, thus achieving the transformation of the UHF-MRI signal. 68,[70][71][72] A typical example is that Li et al recently reported a peptide-based MR probe (TSP) for enhancing UHF T 1 -weighted imaging of M2 macrophages in tumors (Fig.…”
Section: Stimuli-response Regulationmentioning
confidence: 99%
“…31,78 Typically, Mnbased NPs are generally employed as tumor microenvironment-responsive nanoprobes because they can dissociate Mn 2+ ions in an acidic environment, 79 thus enhancing the UHF T 1 imaging signals. 30,74,75 For example, Gao et al designed an octopod-shaped hollow porous manganese(II) oxide (HPMO) NPs as a pH-responsive T 1 -activated nanoplatform for delivery and real-time dynamic tracking of tumorspecific cargoes (Fig. 7a and b).…”
Section: Stimuli-response Regulationmentioning
confidence: 99%
See 1 more Smart Citation